Respuesta :
Answer:
solve for x in the second equation is correct
Step-by-step explanation:
Here is the complete question
Which first step for solving the given system using substitution results in an equation without fractions?
(2x+6y=7
(6x + 18y = 24.... 2
Solve for x in the first equation,
Solve for y in the first equation,
Solve for x in the second equation
The best equation to she will be equation 2 since all the coefficients are end numbers
Let us make x t subject f the formula from equation 2;
From 2: 6x+18y = 24
Subtract 18y from both sides
6x+18y-18y = 24-18y
6x = 24-18y
Divide through by 6
6x/6 = 24/6 - 18y/6
x = 4-3y.
You can see that the resulting expression of x is not a fraction. Hence solve for x in the second equation is correct
Answer:
b
Step-by-step explanation:
edit:
the one after that is b
A= 1
B= 2
C= below